Chemical shift of 129Xe dissolved in red blood cells: Application to a rat model of bronchopulmonary dysplasia. Issue 1 (9th December 2019) - Friedlander, Yonni; Zanette, Brandon; Lindenmaier, Andras; Sadanand, Siddharth; Li, Daniel; Stirrat, Elaine; Couch, Marcus; Kassner, Andrea; Jankov, Robert P.; Santyr, Giles
Abstract : Purpose: To measure the chemical shift of hyperpolarized 129 Xe dissolved in the red blood cells(δRBC ) of a cohort of rats exposed to hyperoxia and intermittent hypoxia (IH) to mimic human bronchopulmonary dysplasia, and to investigate the effect of xenon‐blood distribution time on δRBC . Methods: δRBC was measured from spectra acquired using a chemical shift saturation recovery sequence from 15 Sprague‐Dawley rats exposed to hyperoxia‐IH and 10 age‐matched control rats. Sensitization to the xenon‐blood distribution time was achieved by varying the time between saturation pulses, τ. δRBC was compared with blood fraction measured by histology of the cohort and blood oxygenation measured directly using pulse oximetry following a hypoxic challenge in an identically exposed cohort. Results: The mean δRBC in the hyperoxia‐IH exposed rats was 0.55 ± 0.04 ppm lower than that of the healthy cohort ( P = .0038), and this difference did not depend on τ ( P = .996). The blood fraction of the exposed cohort was lower than that of the healthy cohort ( P = .0397). Oximetry measurements showed that the baseline arterial oxygen saturation (Sa O2 ) of each cohort was not different ( P = .72), but after a hypoxic challenge, the Sa O2 of the exposed cohort was lower than that of the healthy cohort ( P = .003). Conclusion: δRBC is reduced in rats exposed to hyperoxia‐IH compared with control rats. The change in δRBC is consistent with enhanced blood oxygen desaturation of the exposed cohort measured by pulse oximetry during a hypoxic challenge. This suggests that the observed change in δRBC reflects enhanced desaturation in the hyperoxia‐IH exposed cohort compared with the healthy cohort.